Strengthening Fisheries MSMEs for Economic Growth in Mamberamo Hilir District, Mamberamo Raya Regency - Havid Ruslan Samber; J. Ary Mollet; Halomoan Hutajulu (Review of Multidisciplinary Academic and Practice Studies, 2024)
Purpose: This study analyzes the internal and external conditions affecting fisheries micro, small, and medium enterprises in Mamberamo Hilir District and formulates development strategies using Strengths, Weaknesses, Opportunities, and Threats (SWOT)analysis. Methodology: A descriptive qualitative case study design was applied, drawing on in-depth interviews, field observation, and documentation with twenty informants comprising local officials, fishers, fish traders, and consumers, analyzed through a four-stage qualitative SWOT procedure covering factor identification, narrative interpretation, relational mapping, and strategy formulation. Result: The district possesses strong fisheries potential supported by strategic coastal resources and fishing experience, but development is constrained by limited infrastructure, capital, and marketing, despite opportunities from digital technology, market demand, and government support. Conclusions: Fisheries enterprises meaningfully sustain fishing households and generate a measurable local multiplier effect, though this contribution remains below its potential. Limitations: The case study and purposive sample limit generalizability. The study provides a locally grounded framework integrating SWOT analysis with Local Economic Development indicators. Contributions: The study proposes a locally grounded strategy framework linking SWOT to Local Economic Development indicators for an eastern Indonesian fishing community.